Dental anxiety: investigative and management techniques often employed in a cross section of Nigerian Specialist Dental Clinics (2009)
Background: Information on the pattern of dental anxiety’ management in Nigeria is currendy not available. Aim: The study was designed to determine the awareness and frequency of application of dental anxiety assessment questionnaires as well as the current pattern in the management of dental anxiety’ in Nigeria. Methods: The cross-sectional study was conducted using structured questionnaires distributed among dental residents and house officers in Nigerian dental schools. Information requested included demographic variables, frequency of presentation of dental anxiety’, awareness and frequency of application of dental anxiety' questionnaires. The respondents were also asked to rate the frequency of application of the outlined dental anxiety’ management techniques on a 5-point Likert scale. The median score and the range for each technique was determined and compared between the male and female respondents. Results: A total of 96 questionaires were sent out to dental surgeons of all grades. Response was obtained from 86 giving a response rate of 90%. Only 23 (26.7%) respondents were aware of dental anxiety’ questionnaires while only 13 (15.1%) have seen the instrument applied. The percentage of patients with dental anxiety’ was estimated by the respondents to be <20%. Behaviour therapy was the most frequently employed dental anxiety management technique. The female respondents employ behaviour therapy and intramuscular sedation more frequently. Conclusion: The awareness and frequency of application of dental anxiety’ questionnaires appeared poor. Behaviour therapy was the most frequently employed dental anxiety’ management technique. It appears the female respondents employ behavior therapy and intramuscular sedation more frequently.